Heurísticas y método de punto proximal para la reconstrucción automática de geometría en lechos acuáticos - García Bauza, Cristian (2008)
This paper presents several algorithms for the automatic river-bed reconstruction. Navigation channel is defined by a scarce set of bathymetry points which are obtained from several crosssections of the river-bed. At the rendering stage, the scarce depth values and their spatial arrangement generates low-quality polygonal approximations of the real river. In order to preserve realism in the visual representation, a heuristic based on Delaunay and a Proximal Point Method are proposed. Some results obtained for a 400 km cross-section of the Paraná River are included.